Channel accessing and handoff mechanisms in TV white spaces based on channel sensing and database information - Chaitanya K, Krishna; CK, Meghalatha; K, Annapurna; Ramanjaneyulu B, Seetha (International Journal of Engineering and Technology, 2018)
Opportunistic channel accessing and handoff mechanisms are crucial for the successful implementation of cognitive radio networks that depend on vacant channel frequencies of TV white spaces and other primary users. In this work, two such mechanisms that enable quick accessing of vacant channels and cause less interference to primary users are proposed. In these methods, combination of database information and local sensing of channels is used, to know about available vacant channels. If the primary user of incumbent channel returns, the secondary user moves to another vacant channel that is found to be free after scanning. Information from database can be used to speed up the process by limiting the scanning to few probable channels, instead of searching for all. The results show that these methods offer quick handoff of secondary users and cause less interference to primary users.Â Â